Optimizing the Use of Radar when the Ship is Moving in MT. Green Plus: Optimalisasi Penggunaan Radar saat Kapal Berolahgerak di MT. Green Plus - Harahap, Ferry Aulia; Siregar, Muhammad Sapril; Nurman, Salfauqi; Kusturi, Nanda Afra; Nurmala, Eka (PT. Alpha Trianguli Australis, 2024)
It is believed that the high number of collisions in narrow shipping lanes is caused by the lack of skill of sailors. Therefore, this analysis aims to determine the role of Radar in preventing collisions at sea. The research approach is qualitative, and the data will be presented using descriptive analysis. The research findings indicate that the decrease in Radar function is due to the non-implementation of Standard Operating Procedures (SOPs), the officers' lack of understanding of the manual books, and damage to the scanner. The consequences of a decrease in Radar function include navigation hazards because the Radar does not function correctly, making it difficult for the watch crew to identify other ships. To optimize the use of Radar when ships are moving at night, it is necessary to regularly check, maintain and repair navigation equipment.